The Return of the Dead: fascisms in Day of the Oprichnik and New Order - Zorattini, Júlia (2024)
This article aims to investigate the fascist element in Bernardo Kucinski’s A nova ordem [New Order] (2019) and Vladimir Sorokin’s Day of the Oprichnik (2022[2006]). Being respectively classified in the genres of dystopia and antiutopia, these novels do not seek to merely explore the autocratic tendencies sensed in their societies at the time of publication (the Bolsonaro administration and the first term of Putin’s presidency) and warn the reader, but also to reflect on the remnants of authoritarianism imbued in Brazil and Russia’s national cultures. To achieve that effect, these narratives employ an anachronistic mix of high technological development and the resurrection of institutions created in periods of intense political repression, such as DOI-CODI in the Brazilian novel and Ivan the Terrible’s murderous political police, the oprichnina, in the Russian novel. Considering the concepts of “eternal fascism” by Umberto Eco and “working through the past” by Theodor Adorno, we understand that the unending cycles of oppression and violence lived by both countries can be attributed to an ineffective elimination of the social conditions that allow the renovation and restauration of totalitarian structures, of which they are products. As we see it, the meditations proposed by these works of literature are essential in the task of overcoming those ever-returning ghosts.